A Critical Analysis on Causes and Effects of Baseless Adjournments in Pakistan - Javed, Saqib; Iqbal, Muhammad Ahsan; Saleem, Hafiz Abdul Rehman (Pakistan Journal of Humanities and Social Sciences, 2023)
Pakistan is facing a phenomenon of delayed justice which is synonymous to denial of justice. There are several causes for delayed justice, baseless adjournment is one of the leading causes. Baseless adjournment is the postponement of the hearing to the next date on typical reasons. In the criminal justice system, these adjournments are granted due to the absence of a presiding officer, a witness did not appear, the judge was on leave, or there was a lack of prison vans to transport them to court on the date of hearing. In the civil justice system, baseless adjournments are granted due to insufficient laws, the mindset of judges and lawyers, and the accumulation of pending cases. The baseless adjournments lead to the monetary loss of the aggrieved person as well as his precious time and a de facto denial of judicial. The trend of adjournment can be decreased with the amendment in the laws, upgrading infrastructure and management of the court system by the introduction of modern technology including e-court, and an increasing number of courts and judges.